Inventarisasi Tumbuhan Famili Amaryllidaceae Di Taman Sejarah Bandung - Lestari, Savira Puji; Nurani, Shifa; Supriyatna, Ateng (Jurnal Ilmu Pertanian dan Perkebunan, 2023)
Indonesia is an archipelagic country which is famous for its large islands namely Sumatra, Sulawesi, Java, Kalimantan and Papua and includes 34 provinces. Indonesia's biodiversity has put Indonesia in second place after Brazil with the title of Megabiodiversity Country. To maintain this plant diversity, it is necessary to have inventory activities as an effort to collect data for plant species which generally survey locations directly for the sustainability of biological resources as well as planning area management so that these plants are not threatened with extinction. This research was carried out for 1 day on Saturday, 10 June 2023 at the Bandung Historical Park. The method used in this study is a descriptive survey method with exploratory techniques and direct documentation. Based on the results of research conducted at the Bandung Historical Park, it can be concluded that there are 5 species from the Amaryllidaceae family including; Crinum americanum L., Crinum americanum L., Hippeastrum reginae (L.) Herb., Crinum moorei Hook.f., Zephyranthes candida L., Crinum asiaticum L.